If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -19u + -1(-15) = 4 Multiply -1 * -15 -19u + 15 = 4 Reorder the terms: 15 + -19u = 4 Solving 15 + -19u = 4 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -19u = 4 + -15 Combine like terms: 15 + -15 = 0 0 + -19u = 4 + -15 -19u = 4 + -15 Combine like terms: 4 + -15 = -11 -19u = -11 Divide each side by '-19'. u = 0.5789473684 Simplifying u = 0.5789473684
| 20+13q=15q-18 | | x+3(x-7)=1 | | r+8+14r=1+16r | | 9=4+n/4 | | 20+.13q=15q-18 | | 11a-10a+3=15 | | 102-90=25y-31y | | 6v-4v-2=4 | | 6(x+50)+10(x-2)+8(x-10)=7(x-5)+3(x-6)+2 | | 11v-20+17v=18v+20 | | 7f-5=8f+9-2f | | 3y+5=2(y+1)+y | | 7t+6t=61+19-15 | | 3a=0.51 | | 4(z-16)=12 | | 5x-12=2x+24 | | 7y-9=10y+3 | | 4x-66=-2x+90 | | 9z=8z+4 | | 20(x+5)=10(x+5) | | 9-6x-7-15x=5 | | 13=x+(-2) | | 8=-5-n | | 6+7h=9h | | x+3x-14+x+4=180 | | -8+k=-2k+10 | | 6x-(2x+5)=23 | | 5(x+3)=3x+1 | | 7(-7+r)=84 | | 10c-4=3c+6+9c | | 12x+4=12x+10 | | -2-5(5-6n)=-27 |